3(4x+5)-2(6x-1)=17

Simple and best practice solution for 3(4x+5)-2(6x-1)=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+5)-2(6x-1)=17 equation:


Simplifying
3(4x + 5) + -2(6x + -1) = 17

Reorder the terms:
3(5 + 4x) + -2(6x + -1) = 17
(5 * 3 + 4x * 3) + -2(6x + -1) = 17
(15 + 12x) + -2(6x + -1) = 17

Reorder the terms:
15 + 12x + -2(-1 + 6x) = 17
15 + 12x + (-1 * -2 + 6x * -2) = 17
15 + 12x + (2 + -12x) = 17

Reorder the terms:
15 + 2 + 12x + -12x = 17

Combine like terms: 15 + 2 = 17
17 + 12x + -12x = 17

Combine like terms: 12x + -12x = 0
17 + 0 = 17
17 = 17

Add '-17' to each side of the equation.
17 + -17 = 17 + -17

Combine like terms: 17 + -17 = 0
0 = 17 + -17

Combine like terms: 17 + -17 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| c-3=-3+1 | | x^2+y^3=9x-3y^5+10 | | (x)(x+2)(5)=400 | | 8x+21=5x | | 5(x+2)-3x=13+3x | | 3x^4-22x^2-4=0 | | 5x-3xx=2 | | a^2=-2a | | 8x+9+2x-4x=-13-5x | | 2s^2+9s-5=0 | | 16(2x-8)=5(8x+3) | | 5x^2+2x=400 | | n^2-20=-n | | 3+4x+5x=22 | | 7+18z-3=7z+82-2z | | x+4x+4x+3=41 | | v^2=12-v | | (-8y+5)-(-7y-7)=-6 | | 1a(3a+1)+(a+1)(a-1)= | | b^2+6b=16 | | 3A^2-30A+54=0 | | 2x-8=16-x | | -7=7d+21 | | n^2=-3n+4 | | 9x-3-6x=-3+9x | | x^2-10x+5=29 | | 9(12+4z)=-54 | | =(8x^2y-3xy+7xy^2)-(5x^2y+3xy+2xy^2) | | -2(2b+2)+(5b-4)=0 | | (-3d+10)(2d-1)= | | 6x-3G=9 | | 3x^5-7x+2x^6= |

Equations solver categories